MENINGKATKAN HASIL BELAJAR IPS MELALUI PENERAPAN METODE QUESTION STUDENT HAVE (QSH) PADA SISWA KELAS IV SDN 3 MATARAM TAHUN PELAJARAN 2015/2016 - Nila Setiawan; Sudirman Sudirman; Nurhasanah Nurhasanah (Indonesian Journal of Elementary and Childhood Education, 2020)
This research background by lower student social studies learning outcomes. From interviews with fourth grade teacher at SDN 3 Mataram this is due to the quality of learning is still low because teachers often use conventional teaching methods and lack of activity of students in the teaching process. This study aims to improve social studies learning outcomes through the application of the Question Student Have method in grade IV SDN 3 Mataram academic year 2015/2016. Based on the above background, the researchers conduct action research with active learning model type Question Student Have two cycles. Each cycle consists of four phases: planning, action, observation and reflection. Data results obtained through evaluation of student learning, student activities and teacher obtained through observation sheet. From these results it can be concluded that the application of the method Question Student Have IPS can improve learning outcomes in grade IV SDN 3 Mataram. In cycle 1 the amount of the average score of 34.5 students' learning activities with the percentage of 58% categorized quite active, while the average score of 14.5 with the activities of teachers percentage of 73% good category. And the evaluation of student learning outcomes with an average value of 66.7 to 44.7% classical completeness. As for the second cycle of research has increased with the amount of the average score of students' learning activities 45 active category with a percentage of 75%, while the average score of teacher activity with percentage 87.5% 17.5 very good category and the evaluation results of students with average grades -rata 74 with classical completeness 84%. II cycle data are in accordance with predetermined completeness 80%. It can be concluded that the application of active learning model student have the type of question (questions from the students) can improve learning outcomes IPS in grade IV SDN 3 Mataram in academic year 2015/2016.